2018
DOI: 10.3390/cancers10010008
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Epigenetic Histone Acetylation in Hepatocellular Carcinoma

Abstract: Cells respond to various environmental factors such as nutrients, food intake, and drugs or toxins by undergoing dynamic epigenetic changes. An imbalance in dynamic epigenetic changes is one of the major causes of disease, oncogenic activities, and immunosuppressive effects. The aryl hydrocarbon receptor (AHR) is a unique cellular chemical sensor present in most organs, and its dysregulation has been demonstrated in multiple stages of tumor progression in humans and experimental models; however, the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 81 publications
3
21
0
Order By: Relevance
“…On the other hand, the inhibition of HDAC activity keeps a continuous expression of a target gene. In this context, the control of HDAC activity by HDAC inhibitors has been targeted for the development of anticancer strategies as well as therapies for human diseases derived from cardiovascular, metabolic, and neurodegenerative disorders [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the inhibition of HDAC activity keeps a continuous expression of a target gene. In this context, the control of HDAC activity by HDAC inhibitors has been targeted for the development of anticancer strategies as well as therapies for human diseases derived from cardiovascular, metabolic, and neurodegenerative disorders [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of HCC patients are diagnosed in advanced stages of the disease, and the poor survival in patients with HCC can be largely attributed to rapid intrahepatic recurrence due to cancer metastases (24). HDAC inhibitors, including trichostatin A and vorinostat, induce cell death but simultaneously augment cell migration and metastasis to ruin therapeutic efficacy via activating protein kinase C signaling (25).…”
Section: Discussionmentioning
confidence: 99%
“…The current investigation indicated that deregulation of HATs and histone HDACs is engaged in the progression of a range of cancers, making them spur the considerable interest of the research community [22,85]. Thus, HDACis become appealed target in attempts to attenuate many human cancers including colorectal cancer.…”
Section: Histone Deacetylase Inhibitors and The Treatment Of Colorectmentioning
confidence: 94%